2015
DOI: 10.1177/0954406215621099
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of temperature-dependent mechanical properties of magnetorheological fluids using a parallel disk shear stress testing device

Abstract: Mechanical properties are critical to the working performance of magnetorheological fluids (MRFs), especially in high temperature situations. This paper presents an experimental investigation to analyze the effects of temperature on mechanical properties of MRFs. First, a parallel disk method was implemented for the shear stress measurement of MRFs and the measurement principle was theoretically illustrated. Then, a detailed introduction to the MRF sample preparation and the testing device development was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…But, a large thermal expansion of carrier fluid was realised at higher temperatures. Also, degradation in the performance of MR fluid was found when the sample was subjected to cyclic temperature [17]. Gao et al [18] presented geometric optimisation of MR damper for prosthetic knees using particle swarm optimisation to reduce the energy consumption and weight reduction.…”
Section: Introductionmentioning
confidence: 99%
“…But, a large thermal expansion of carrier fluid was realised at higher temperatures. Also, degradation in the performance of MR fluid was found when the sample was subjected to cyclic temperature [17]. Gao et al [18] presented geometric optimisation of MR damper for prosthetic knees using particle swarm optimisation to reduce the energy consumption and weight reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that on mixing smaller and larger particles with different weight fractions, the Bingham yield stress value increases by a factor of three compared with large-sized particles dispersed in fluid [38,39]. The finding implies the mechanical properties of MR fluids are the function of temperature; the steps involved in bringing down the off-state viscosity and shear stress at elevated temperatures were studied, as was the performance degradation for a low-high-low temperature cycle [40]. To synthesize MR fluid, the following steps were followed:…”
Section: Synthesis Of Mr Fluidsmentioning
confidence: 99%
“…Wang et al, 24 carried out simulation on transient temperature induced in MR clutch and developed a liquid cooling system for dissipation of heat for this system. Wang et al, 25 observed performance reduction of MR fluids when subjected to working temperature of more than 150°C and an attempt was made to measure the changes in mechanical properties of MR fluid when subjected to temperature changes. Chen et al, 26 proposed a novel model of self-powered MR damper for motorcycle application which can produce a useful electrical energy from wasted mechanical energy.…”
Section: Introductionmentioning
confidence: 99%